A Review of Molecular Approaches for Sex Determination in Ornamental Fish - I Dewa Agung Panji Dwipayana; Ni Luh Putu Kayika Febryanti; I Gusti Ayu Nadia Prasta Unique (Program Magister Ilmu Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
The ornamental fish industry is a globally significant sector of aquaculture in which accurate sex identification is essential for optimizing breeding efficiency, economic value, and stock management. However, traditional phenotypic sexing methods are often unreliable due to late sexual dimorphism, environmental influences, and extensive strain divergence driven by domestication and selective breeding. This review synthesizes current knowledge on the biological basis of sex determination in ornamental fishes and evaluates molecular approaches used for sex identification across diverse genetic and environmental contexts. Teleost fishes exhibit exceptional diversity in sex determination systems, including XX/XY, ZZ/ZW, polygenic, and epigenetic system. Such diversity is often accompanied by selective breeding which may shuffle sex-determining regions. Consequently, no single molecular marker is universally applicable across ornamental taxa. PCR-based methods, such as SCAR, RAPD, AFLP, and InDel markers, remain the most accessible tools and are effective within validated populations, while next-generation sequencing enables genome-wide discovery of sex-linked SNPs and structural variants to provide high-resolution and reproducible diagnostics. Transcriptomic and epigenetic markers offer mechanistic insight into sex differentiation particularly in plastic or temperature-sensitive systems, although they are limited as standalone diagnostic tools. Emerging portable and point-of-care platforms show promise for on-site sex identification but require further validation in fish. This review emphasizes that robust molecular sexing in ornamental fish requires careful marker selection, multi-strain validation, and integration of genetic, epigenetic, and environmental data. Expanding genomic resources and standardized validation frameworks will be critical for translating molecular sexing into reliable, industry-wide applications.